Who is more water insecure? Gendered evidence from urban Pakistan - Khalid, Sidra; Hafeez, Mohsin; Aqib, Sohaib (Frontiers in Water, 2024)
Gender and social dimensions of access to and use of water resources are often overlooked in policy and programming despite their importance in shaping water security. This study examines factors affecting water security in urban Pakistan through a gender lens. We surveyed 560 men and women in two towns in Islamabad and Rawalpindi facing water and sanitation challenges. Through a binary logit model and marginal effects analysis, we analyzed the relationship between water security and multiple variables, including gender, education, age, employment status, payment for water, urban wealth quintile, drinking water source, individual water concern level, water satisfaction, and water quality perception. While more than 50 percent of both genders experience water insecurity, the prevalence of water insecurity is notably higher among women. Men in the surveyed population had higher levels of employment, wealth, and education levels compared to women. The regression analysis across both genders reveals that paying for drinking water negatively and significantly impacts water security, while concern about future water issues, satisfaction with drinking water, and water quality significantly and positively impact water security levels. For women specifically, access to improved drinking water sources, higher education levels, and employment significantly improve their water security level, underscoring the importance of promoting women's education and economic empowerment. For men, age and wealth levels emerged as significant factors impacting their water security, with older men more vulnerable to water insecurity than younger men and women. These findings underscore the complex interplay of individual, social, and structural dynamics shaping water security experiences, emphasizing the need for gender-responsive and intersectional approaches to water interventions in urban Pakistan and beyond. Equitable water policies and programs necessitate the collection of more disaggregated data. This study marks the first application of the Individual Water Insecurity Experiences (IWISE) Scale used in Pakistan's urban context, with recommendations for its broader implementation to improve decision-making that can lead to sustainable water solutions across diverse gender and social groups.